Optimisation of Species Selection at Prinslust Game Farm - Bouwer, Lene (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2015)
Selecting the best combination of scarce game that will maximize profit over a specific time